Comparing the effects of aromatherapy massage and inhalation aromatherapy on anxiety and pain in burn patients: A single-blind randomized clinical trial. Issue 8 (December 2016) - Seyyed-Rasooli, Alehe; Salehi, Feridoon; Mohammadpoorasl, Asghar; Goljaryan, Sakineh; Seyyedi, Zahra; Thomson, Brian
Highlights: Aromatherapy massage and inhalation reduce anxiety and pain of patients with burns. Combination of both methods is proposed for noninvasive nursing care of patients. Inhalation aromatherapy is more effective in reducing anxiety. Aromatherapy massage is more effective in reducing pain. Abstract: Background: Anxiety and pain are recognized as major problems of burn patients; because pharmaceutical treatments for controlling anxiety and pain symptoms lead to complications and an increase in health costs, nonpharmacological nursing interventions were considered for this group of patients. This led to the present study aimed at comparing the effect of aromatherapy massage with inhalation aromatherapy for anxiety and pain in burn patients. Methods: This single-blind clinical trial was carried out on 90 patients with burns <20%. Patients were randomly assigned to one of three groups, namely aromatherapy massage, inhalation aromatherapy, and control group. The patients assigned to the aromatherapy massage group received a massage for half an hour using a blend of lavender and almond oils, while a blend of rose and lavender aroma was used for the inhalation aromatherapy group. Spielberger State Anxiety Inventory was used for measuring anxiety and the visual analog scale (VAS) scale was used for measuring pain. Results: The results showed that three groups were equal in terms of demographics, disease characteristics, and scores of anxiety and pain at the baseline. The mean decreases of anxiety scores were −0.04 ± 5.08, 6.33 ± 12.55, and 6.43 ± 10.60 in the control group, aromatherapy massage group, and inhalation group, respectively ( p  = 0.007). The mean decrease of pain scores were −0.10 ± 0.96, 1.70 ± 1.84, and 0.97 ± 1.56 in the control group, aromatherapy massage group, and inhalation group, respectively ( p  < 0.001). Conclusion: The study results showed the positive effect of aromatherapy massage and inhalation aromatherapy compared with the control group in reducing both anxiety and pain of burn patients. Therefore, both interventions, which are inexpensive, and noninvasive nursing tasks can be proposed for alleviating anxiety and pain of burn patients.